Prospective study trial to increase the diagnostic accuracy of stroke among patients presenting to the emergency room with acute dizziness, vertigo and floating sensation -efficacy of "disequilibrium template" - Yasui, Keizo; Kawabata, Kazuya; Inada, Shinji; Ito, Daisuke; Mitsuma, Norimasa; Hattori, Makoto; Yokoi, Satoshi; Yamada, Shinichiro; Noguchi, Yoshinori; Hasegawa, Yasuhiro; Nishi, Ryoji; Nakai, Noriyoshi (Japanese Journal of Stroke, 2013)
Background and Purpose: We prepared and operated the "disequilibrium template" for non-specialists to increase the diagnostic accuracy of stroke among patients presenting to the emergency room with acute dizziness, vertigo or floating sensation. The purpose of this prospective study was to examine the efficacy of the "disequilibrium template." Methods: Between January 2011 and December 2011, we conducted a prospective study of 487 patients who acutely complained dizziness, vertigo or floating sensation in the emergency room. Result: Stroke was diagnosed in 11.7% (57 of 487) of all patients with acute dizziness, vertigo or floating sensation. On admission, false-negative diffusion-weighted MRI was found in 10.5% (6 of 57) of patients with acute stroke. Nevertheless, we were able to diagnose stroke among all patients at the first visit to the emergency room. 66.5% (262 of 394) of patients without stroke diagnosed in the emergency room revisited as outpatient, and they were all reaffirmed without stroke. Using the "disequilibrium template" in the emergency room prevented us from overlooking stroke. Conclusions: This study revealed that the "disequilibrium template" is very simple and useful tool for increasing the diagnostic accuracy of stroke among patients with acute dizziness, vertigo or floating sensation.